1975
DOI: 10.1071/ar9750011
|View full text |Cite
|
Sign up to set email alerts
|

Studies of grain production in Sorghum bicolor (L. Moench). III.* The relative importance of assimilate supply, grain growth capacity and transport system

Abstract: In field and glasshouse experiments with grain sorghum (cv. RS610), the assimilate supply was varied by increasing or decreasing radiation and carbon dioxide supply; the potential grain storage capacity was altered by spikelet removal; and the transport system was reduced by incision of the culm. Plants grown at four population densities in the field were manipulated to increase (by removing neighbouring plants) or decrease (by shading) the supply of photosynthates during grain filling. These treatments affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The differences in grain yield manifested through differences in total biomass and HI can be examined using the source–sink framework that considers contributions from both assimilation during grain filling and remobilization of preanthesis assimilate. In sorghum, this source–sink framework is exemplified by the studies of Fischer and Wilson (1975) The differences in total biomass at maturity among experiments in this study, and hence the major differences in yield, may be explained predominantly by differences in assimilation during the grain‐filling period. Differences in assimilation during this period were consistent with the observation that total biomass at anthesis did not differ as much among experiments as total biomass at maturity (Table 3).…”
Section: Resultsmentioning
confidence: 85%
“…The differences in grain yield manifested through differences in total biomass and HI can be examined using the source–sink framework that considers contributions from both assimilation during grain filling and remobilization of preanthesis assimilate. In sorghum, this source–sink framework is exemplified by the studies of Fischer and Wilson (1975) The differences in total biomass at maturity among experiments in this study, and hence the major differences in yield, may be explained predominantly by differences in assimilation during the grain‐filling period. Differences in assimilation during this period were consistent with the observation that total biomass at anthesis did not differ as much among experiments as total biomass at maturity (Table 3).…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, Bonus may have a more efficient phloem transport system and could have used the surplus assimilate to increase the individual grain weight despite having reduced grain number per panicle after night chilling. Fischer and Wilson (1975) manipulated photosynthate supply during grain filling in sorghum. Removal of spikelets at three‐quarter anthesis increased the size of the remaining grains at maturity.…”
Section: Discussionmentioning
confidence: 99%
“…While final caryopsis weight could, in theory, be related to grain-filling rate, duration, or both, the length of the effective filling period (EFP) appears to be similar for various sorghum hybrids (Quinby, 1972;Kiniry, 1988;Heiniger et al, 1993). Previous sorghum research has shown that grain-filling rate is affected by the number of sinks to be filled (Kiniry, 1988;Heiniger et al, 1993), assimilate supply during the EFP, and feedback mechanisms originating in the caryopses (Fischer and Wilson, 1975;Muchow and Wilson, 1976;Heiniger et al, 1993). As the feedback relations are, as yet, unclear, we decided to model caryopsis weight empirically.…”
mentioning
confidence: 99%